2009
DOI: 10.1261/rna.1926510
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Hen1 is a 3′ terminal RNA ribose 2′-O-methyltransferase component of a bacterial RNA repair cassette

Abstract: Hen1 is an RNA ribose 29-O-methyltransferase that modifies the 39 terminal nucleoside of eukaryal small regulatory RNAs. Here, we report that Hen1 homologs are present in bacterial proteomes from eight different phyla. Bacterial Hen1 is encoded by the proximal ORF of a two-gene operon that also encodes polynucleotide kinase-phosphatase (Pnkp), an RNA repair enzyme. Purified recombinant Clostridium thermocellum Hen1 is a homodimer of a 465-amino acid polypeptide. CthHen1 catalyzes methyl transfer from AdoMet to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
50
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 37 publications
2
50
0
1
Order By: Relevance
“…Recent studies suggest a capacity for this type of ''intelligent'' RNA repair mechanism in the many bacterial species that encode the repair enzymes Pnkp (polynucleotide 59-kinase/39-phosphatase) and Hen1 in an operon-like gene cassette (Chan et al 2009a;Jain and Shuman 2010). Bacterial Pnkp was first discovered in Clostridium thermocellum and the CthPnkp protein has been characterized extensively as the exemplary bacterial end-healing enzyme (Martins and Shuman 2005;Shuman 2006a,b, 2007;.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies suggest a capacity for this type of ''intelligent'' RNA repair mechanism in the many bacterial species that encode the repair enzymes Pnkp (polynucleotide 59-kinase/39-phosphatase) and Hen1 in an operon-like gene cassette (Chan et al 2009a;Jain and Shuman 2010). Bacterial Pnkp was first discovered in Clostridium thermocellum and the CthPnkp protein has been characterized extensively as the exemplary bacterial end-healing enzyme (Martins and Shuman 2005;Shuman 2006a,b, 2007;.…”
Section: Introductionmentioning
confidence: 99%
“…The N-terminal half is conserved among the bacterial Hen1 homologs only. Our physical and functional characterization of Clostridium thermocellum Hen1 (CthHen1) has revealed the following (Jain and Shuman 2010). (1 Raven Huang's lab has studied Anabaena variabilis Hen1 methyltransferase and its connection to Anabaena Pnkp; they showed that the AvaHen1-AvaPnkp complex has endhealing and sealing activities on a broken tRNA substrate and that ribose 29O-methylation of the 39 end prior to sealing can protect the repair junction from further damage by a transesterifying ribotoxin (Chan et al 2009a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The capacity for protective immunity during RNA repair is illustrated by the many bacterial species that encode the repair enzymes Pnkp (polynucleotide 5′-kinase/3′-phosphatase) and Hen1 in an operon-like gene cassette (6,7) (Fig. 1A).…”
mentioning
confidence: 99%
“…C. thermocellum Hen1 is a a 465-aa polypeptide. The C-terminal half of CthHen1 is an autonomous manganesedependent 3′-terminal ribose 2′O-methyltransferase (7,12,13). The N-terminal half of CthHen1 has no known enzymatic activity.…”
mentioning
confidence: 99%